2016
DOI: 10.4037/ccn2016560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Head Elevation Protocols Following Femoral Artery Sheath Removal After Coronary Angiography

Abstract: OBJECTIVES To compare 2 standard protocols for head elevation following removal of a femoral artery sheath after coronary angiography and their effects on bleeding complications and reported levels of back pain. One protocol involved flat supine bed rest; the other allowed progressive head elevation. METHODS A prospective comparative study of 80 adult patients undergoing coronary angiography via the femoral approach. The Numeric Rating Scale was used as the measure of reported pain. RESULTS No bleeding complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In this study, it was seen that the application of cold after PCI decreased the incidence of pain in the femoral artery region. In other studies, pain associated with coronary angiography developed mostly on the back during catheter withdrawal and at rest [2,14,32,52,53]. In addition, the patients reported that the use of a sandbag and staying in bed for a long time was disturbing and painful [35].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was seen that the application of cold after PCI decreased the incidence of pain in the femoral artery region. In other studies, pain associated with coronary angiography developed mostly on the back during catheter withdrawal and at rest [2,14,32,52,53]. In addition, the patients reported that the use of a sandbag and staying in bed for a long time was disturbing and painful [35].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Most studies outline predictors and interventions to address musculoskeletal pain associated with cardiac catheterization, aimed at postprocedural care (bedrest, positioning, etc). [11][12][13] Our findings add to the existing literature by demonstrating that procedural sedation administration practices may practicably reduce the overall total dosage of procedural sedation medications required, without compromising patient satisfaction or comfort.…”
Section: Discussionmentioning
confidence: 52%
“…A literature search of contemporary studies that characterize subjective patient experiences during invasive cardiac procedures revealed few articles, and the majority of available studies fail to fully capture important differences in intraprocedural factors . Most studies outline predictors and interventions to address musculoskeletal pain associated with cardiac catheterization, aimed at postprocedural care (bedrest, positioning, etc) . Our findings add to the existing literature by demonstrating that procedural sedation administration practices may practicably reduce the overall total dosage of procedural sedation medications required, without compromising patient satisfaction or comfort.…”
Section: Discussionmentioning
confidence: 82%
“…The study showed that the intervention group, who had early mobility and position changes earlier than 6 hours, reported less urinary retention and less average pain [8]. However, another study has found that changing the patient's position did not affect the severity of back pain in patients with back pain [9]. Studies have shown that early mobilization of patients after angiography results in fewer pain symptoms, fewer postoperative complications, and higher satisfaction [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 96%